Platformní flotily: revoluční zaměstnávání, nebo snaha o obcházení zákona? - Žaneta Hošková (Acta Universitatis Carolinae. Iuridica)
Although a lot has already been said about the collaborative economy and the virtual platforms that are its product, the article deals with a topic that has not been discussed so far – it deals with the so-called platform fleets and ways of dealing with their own workforce. The aim of the article is, first of all, to point out the widespread practices of virtual platforms, which consist in using the work of platform fleet employees. Subsequently, analyze the formal setting of relations between all participating entities, compare them with the actual state and with the desired state. It debates whether the activity of these fleets can show signs of illegal activity, or whether it is necessary to hold back with the judgments about illegal activity and consider the method of fleet employment as a necessary revolution in the form of employment de lege ferenda.